The Phenomena of Learning Loss Experienced by Elementary School Students during the Covid-19 Post Pandemic - I Wayan Kertih; I Wayan Widiana; I Gede Wahyu Suwela Antara (Emerging Science Journal, 2023)
The COVID-19 pandemic caused most students to experience learning loss after joining online learning for almost 2 years. Learning loss is a student's condition experiencing learning setbacks academically due to the factors of the non-sustainable educational process. The study aimed at analyzing the learning loss phenomenon experienced by elementary school students in the COVID-19 post-pandemic situation. The study used a descriptive qualitative approach. The population of the study was 401,321 distributed students, and the sample was gained through conducting two sampling techniques, such as random cluster sampling and accidental sampling, with a final sample of 1,104 students. The data collection methodologies conducted were interview, observation, and questionnaire. The questionnaire used contained 15 questions that had been validated before. The data analysis of the study was conducted interactively using 3 techniques, such as data reduction, data display, and drawing conclusions. The descriptive analysis was conducted by using the Guttman scale with the percentage statistic technique. The result of the study showed that there were learning loss phenomena in the post-pandemic situation, a condition seen from the researched dimensions in the low and medium categories. Moreover, a high level of learning loss was found in the rural area. This was observed from several things, such as the learning facilities provided, the parent's role, and the learning methodologies conducted. To resolve learning loss, we need to participate all parties in the learning process, which in this context means mending a good relationship with the community and parents to improve the learning quality, which is assisted with innovative learning models. Doi: 10.28991/ESJ-2023-SPER-014 Full Text: PDF